LEGAL POLITICAL OF WELL-KNOWN TRADEMARK PROTECTION REVIEWED FROM DEVELOPMENT OF TRADEMARK LAW IN INDONESIA TO AVOID FRAUDULENT COMPETITION - Moch Alfi Muzakki; Kholis Roisah; Rahandy Rizki Prananda (LAW REFORM, 2018)
The achievement of a Trademark in order to become famous is not an easy job, the obstacle of building a Trademark into a well-known trademark is a factor that encourages the emergence of fraudulent competition that is detrimental to others. The Issuance  of Law No. 20 of 2016 concerning Trademarks and Geographical Indications is deemed unable to accommodate fraudulent competition. This study aims to examine the law politics of famous Trademark protection in terms of the development of Trademark law in Indonesia and to compare the protection of famous Trademarks in Indonesia with other countries to avoid fraudulent competition in the use  Trademarks. This study is applied a normative juridical approach. The results of the study show that even though Indonesia has made  amendment toward Trademark Law (UUM) 5 times, there is no specific definition of a well-known brand within  Indonesia. Indonesia does not yet have arrangements regarding fraudulent competition in the brand, even though Indonesia has anti-competition laws, but fraudulent competition in Indonesia does not use it as a legal basis.Keywords: Trademark; Well-Known Trademark;  Fraudulent Competition.